DNA Barcoding and Morphological Characters of Juvenile Plectropomus (Perciformes: Epinephelidae) Caught in Makassar Strait - Mainna, Muth; Kadir, Nadiarti Nurdin; Husain, Aidah Ambo Ala; Hidayani, Andi Aliah; Umar, Widyastuti; Moore, Abigail Mary (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research Integrated DNA barcoding and morphological variations can improve the identification of grouper species. DNA barcoding confirms the morphological identification of Plectropomus (98-100% similar). High intraspecies genetic diversity revealed within Plectropomus in Makassar Strait. Potential cryptic species identified within Plectropomus based on genetic analysis. Abstract The high economic value of groupers has made them a popular choice in both local and international markets. However, identifying grouper species is also challenging due to complex morphological variations especially in the juvenile phase. An integrative approach combining DNA barcoding and morphometric analysis was applied to improve species identification accuracy and provide additional information on grouper stocks. This research aims to gain a deeper understanding of the morphological and genetic diversity of groupers caught in the juvenile phase from the Makassar Strait. Samples of the genus Plectropomus (n=6) collected from a fish landing site in Pangkajene Kepulauan Regency were identified based on morphology and using molecular methods (DNA barcoding). Phylogenetic and haplotype network analyses were performed. For all specimens the morphometric-meristic and molecular analyses were consistent (98-100% similarity) to known P. leopardus and P. oligacanthus accessions from GenBank. However, phylogenetic analysis: P. leopardus clustered into two distinct lower-level clades, and notably, two P. areolatus (Taiwan) resolved within the P. leopardus clade, while two P. laevis (Philippines) the resolved within the P. oligacanthus clade. Haplotype network showed high intraspecific genetic diversity, with P. leopardus forming four distinct haplotype groups and P. oligacanthus forming two groups. These findings collectively indicate that misidentification may be common and highlight the urgent need for further investigation into geographic barriers to gene flow and the potential existence of cryptic species or subspecies within Plectropomus. This study is expected to provide critical support for sustainable fisheries management and the conservation of marine biodiversity in the Makassar Strait.